Targeting necroptosis in Alzheimer’s disease: can exercise modulate neuronal death? - Donglei Lu; Wenyu Zhang; Ruiyu Li; Sijie Tan; Yan Zhang (Frontiers in Aging Neuroscience)
Alzheimer’s disease (AD) is a neurodegenerative disorder characterized by cognitive decline and neuronal degeneration. Emerging evidence implicates necroptosis in AD pathogenesis, driven by the RIPK1-RIPK3-MLKL pathway, which promotes neuronal damage, inflammation, and disease progression. Exercise, as a non-pharmacological intervention, can modulate key inflammatory mediators such as TNF-α, HMGB1, and IL-1β, thereby inhibiting necroptotic signaling. Additionally, exercise enhances O-GlcNAc glycosylation, preventing Tau hyperphosphorylation and stabilizing neuronal integrity. This review explores how exercise mitigates necroptosis and neuroinflammation, offering novel therapeutic perspectives for AD prevention and management.